Severe acne associated with osteoarticular inflammation (S.A.P.H.O. syndrome). - Bonifazi, E.; Milano, A.; Inverardi, D. (European Journal of Pediatric Dermatology, 2004)
S.A.P.H.O. syndrome (Sinovitis, Acne, Pustulosis, Hyperostosis, Osteitis) underlines the relationship between osteoarticular inflammation and disorders with neutrophilic leucocytosis, also reported in children (1, 2, 3). The latter, including severe acne and amicrobic pustulosis, are always associated to necrotic phenomena, which are expression of vasculitis. The most frequent osteoarticular manifestations of the syndrome such as anterior thoracic osteomyelitis, sterno-clavear, sacro-iliac and knee arthritis are characterized by variable severity. Vasculitic phenomena, joint involvement and the significantly increased indexes of inflammation are expression of an immune allergic reaction. This explains the positive response to corticosteroid, but not to antibiotics. Isotretinoin cannot be considered as responsible for this syndrome, which occurs even without this treatment.